Toxic Effects of p-Chloroaniline on Cells of Fungus Isaria fumosorosea SP535 and the Role of Cytochrome P450 - Shicong Huang; Jiahui Gao; Lin Zhou; Liujian Gao; Mengke Song; Qiaoyun Zeng (Toxics, 2025)
Efficient methods to remediate PCA (p-chloroaniline)-polluted environments are urgent due to the widespread persistence and toxicity of PCA in the environment. Microbial degradation presents a promising approach for remediating PCA pollution. However, the PCA-degrading fungi still have yet to be explored. This study confirmed the highly PCA-degrading efficiency of an isolated fungus, Isaria fumosorosea SP535. This fungus can achieve a PCA degradation efficiency of 100% under optimal conditions characterized by an initial PCA concentration of 1.0 mM, pH of 7.0 and a temperature of 25 °C. SEM and TEM analyses revealed that the toxicity of PCA resulted in roughened surfaces of Isaria fumosorosea SP535 hyphae, voids in the cytoplasm, and thickened cell walls. PCA addition significantly elevated the activities of cytochrome P450 monooxygenase in both cell-free extracts and microsomal fractions in the media, suggesting the important role of the P450 system in PCA metabolization by Isaria fumosorosea SP535. The results provide a microbial resource and fundamental knowledge for addressing PCA pollution.